Forming the Character of Youth During Pandemic Through Social Media Literacy in Pekanbaru - Risdayati, Risdayati; Arief, Yanwar (Devotion : Journal of Research and Community Service, 2022)
During the pandemic, teenagers stay at home for 24 hours and carry out activities, especially communicating and interacting via gadgets or smartphones. All information and interactions occur in one direction, this indirectly affects the behavior of teenagers, especially if they see negative content. Positive literacy by involving adolescents is one option in shaping the positive character of adolescents so as to prevent negative things from happening. The purpose of this study was to analyze the formation of adolescent character during the pandemic through existing social media literacy, including Instagram, Youtube, and others by involving the relevant agencies, namely the Communications and Information Office and the Library and Archives Service as well as academics. The results of this study indicate that indirectly involving adolescents in this activity is expected to provide literacy and positive information on the character and behavior of adolescents. Several forms and themes from Jelita, namely Riau Literacy and Information for Superior Human Resources (Riau LITE SDM Unggul), Promise Heart, Obrol Obrol (O2), Family Room. It is hoped that this program will be able to provide literacy and information and education to teenagers to serve as a basis for behavior so that they have a positive character.